2007
DOI: 10.1080/00048670701579082
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Masculinity, Culture and the Diagnosis of Depression

Abstract: Amongst the hypotheses to explain these findings are those relating to service utilization, rater bias, criteria bias, and cultural pathoplastic effects. These questions need answers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
7
1
Order By: Relevance
“…Within the patient cohort, the Maori rate for violent offending (51%) was significantly less than was that for NZ Europeans (71%). This contrasts with an earlier New Zealand study of general New Zealand psychiatric service users which found that the highest ratings assigned by clinicians for over activity/aggression on the HoNoS were to Maori males, followed by Maori females [9].…”
Section: Discussioncontrasting
confidence: 98%
“…Within the patient cohort, the Maori rate for violent offending (51%) was significantly less than was that for NZ Europeans (71%). This contrasts with an earlier New Zealand study of general New Zealand psychiatric service users which found that the highest ratings assigned by clinicians for over activity/aggression on the HoNoS were to Maori males, followed by Maori females [9].…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, these stressors and social pressures make the university education more stressful event for males than for females (Dehshiri et al., ; Khodayari‐Fard et al., ; Rezai‐Adriany et al., ). It is possible that these gender differences may be due to different ways of coping with stressors (Pillay & Ngcobo, ) or due to different help‐seeking behaviours (Mellsop & Smith, ; Tapsell & Mellsop, ).…”
Section: Discussionmentioning
confidence: 99%
“…The unclear gender‐based prevalence is due to the different assessment tools used by the researchers (Ghasemzadeh, Mojtabai, Karamghadiri, & Ebrahimkhani, ). The depression rate and gender‐based prevalence are still unclear in Iran and warrant further investigation (Mellsop & Smith, ).…”
mentioning
confidence: 99%
“…Much debate about culture has centred on diagnostic issues, for example culture‐bound syndromes and the pathoplastic effect of culture on disorders (e.g. Strakowski et al ., ; WHO, ; Mellsop and Smith, ; Udomratn, ). However, of more universal relevance is the effect of culture on illness behavior and on attitudes towards mental health services.…”
Section: Formulationmentioning
confidence: 99%